Climatic response of Guadalupe cypress (Hesperocyparis guadalupensis) in Guadalupe island, Baja California, Mexico - Villanueva Díaz, José; Cerano Paredes, Julián; Olivares Bañuelos, Nadia C.; Valles Pérez, Miguel; Stahle, David W.; Cervantes Martínez, Rosalinda (Instituto de Ecología, A.C., 2015)
A climate-sensitive ring-width chronology of the endemic Guadalupe cypress (Hesperocyparis guadalupensis) was developed for the Guadalupe Island. The chronology length covers the last 205 years (1804-2008) and was significantly correlated (r = 0.45 a 0.48, p<0.000) with ring-width chronologies from the areas of Baja California, California, and southern Canada formerly used to analyze the influence and for reconstruction purposes of the PDO. This association was weak and non-significant with chronologies developed along the western slopes of the Sierra Madre Occidental, probably influenced by other circulatory patterns. The cypress chronology showed a significant association with instrumental (r= 0.414, P<0.000, n = 109) and reconstructed (r= 0.68 p<0.000, n= 109) indices of the PDO. The chronology was significantly associated (r= 0.65, p<0.0005, n= 44) with the January-November precipitation for weather stations in Ensenada indicating potential for climate reconstructions. The spectral analysis of the ring-width chronology detected significant peaks at frequencies from 12 to 28 years and 50 to 70 years which are associated to the PDO effect, and peaks of 6.8 more related to the ENSO effect. The location of the chronology at the southern extreme of the PDO influence area may be important to analyze in greater detail the impact of the PDO and other atmospheric phenomena such as ENSO. The observed climatic response of cypress opens new research opportunities for paleoclimatic studies and may be useful to plan for restoration and conservation actions of this and other associated species.